Quality and functional properties of ‘Tupy’ blackberry stored in modified atmosphere conditions Qualidade e propriedades funcionais de amora-preta ‘Tupy’ armazenada em condições de atmosfera modificada - Soethe C.* (2019)
© All the contents of this journal, except where otherwise noted, is licensed under a Creative Commons Attribution License.The aim of this work was to evaluate the effect of storage temperature, in passive modified atmosphere (MA) and atmospheric composition in active MA on quality maintenance, total phenolic compounds (TPC) and total antioxidant activity (TAA; DPPH and ABTS methods) of ‘Tupy’ blackberry. Two experiments were carried out. In experiment 1, the fruit were stored for eight days at 0, 5 and 10 °C in passive MA. In experiment 2, the initial atmospheres of 21.0 kPa O2 + 0.04 kPa CO2 (passive MA); 9.2 kPa O2 + 9.2 kPa CO2 (active MA with high CO2); 1.4 kPa O2 + 0.04 kPa CO2 (active MA with low O2); and 1.4 kPa O2 + 9.6 kPa CO2 (active MA with low O2 + high CO2) were evaluated for eight days at 0 °C. In both experiments, the fruit were packed in Xtend® plastic films. After eight days of storage in passive MA, temperatures of 0 and 5 ºC provided fruit with higher force to compression and titratable acidity (TA) and lower soluble solids/titratable acidity ratio (SS/TA), but with lower values of TPC and TAA (DPPH method) when compared to the temperature of 10 °C. The fruits stored at 0 °C presented lower values of weight loss and incidence of decay. Blackberries stored for eight days at 0 °C, in active MA with low O2, associated or not with high CO2, presented lower respiration rate and higher values of TPC and TAA (DPPH method), but did not differ in the values of incidence of decay, force to compression, SS, TA, SS/TA ratio and color attributes when compared to active MA with high CO2 and passive MA.